O tombamento do conjunto arquitetônico e urbanístico de São João Del-Rei: negociação e conflito entre projetos de apropriação e uso do patrimônio cultural (1938-1967) - Denis Pereira Tavares (2012)
The aim of this paper is to describe and elucidate the tensions arising from the preservation ofthe architectural and urban joint of São João del-Rei between the years 1938 and 1967, in anenvironment of accelerated transformation of the city's urban landscape. We sought toinvestigate how was the implementation and conduct of policies for the preservation ofcultural heritage in São João del-Rei, as well as the relationship between the actors involvedwith this practice, in this case, the technicians of the Department of National Historical andArtistic Heritage (SPHAN) and the local social workers gathered around the relational spaceof the Commercial Association of São João del-Rei. Our premise is that the selection of itemsto be preserved and defined as a cultural heritage is a political operation that always involvestensions, negotiations and conflicts of interest. From this perspective, we note the emergenceof a field of conflict over borders and forms of use, ownership and possession of symbolicgoods in the city of São João del-Rei. In this field, actors with different projects ofappropriation and use of the city have disputed the very definition of the power of objects thatcould legitimately be sanctioned as "heritage" and thus worthy of being transmitted to futuregenerations.